Respuesta :

[tex]9x^2y^2=x^2y^2\cdot9\\\\5x^2y^3=x^2y^2\cdot5y\\\\GCF(9x^2y^2;\ 5x^2y^3)=x^2y^2[/tex]

Answer: GCF of [tex]9x^2y^2\ and\ 5x^2y^3[/tex] is [tex]x^2y^2[/tex]

Step-by-step explanation:

Since we have given that

[tex]9x^2y^2\ and\ 5x^2y^3[/tex]

We need to find the GCF of the above expression:

GCF denotes the greatest common factor.

Here,

Factors of [tex]9x^2y^2=9\times x\times x\times y\times y[/tex]

Factors of [tex]5x^2y^3=5\times x\times x\times y\times y\times y[/tex]

So, GCF of [tex]9x^2y^2\ and\ 5x^2y^3[/tex] is [tex]x^2y^2[/tex]